Protective effect of metoclopramide against organophosphate‐induced apoptosis in the murine skin fibroblast L929. Issue 3 (13th October 2017) - Jaber, Basem M.; Petroianu, Georg A.; Rizvi, Syed A.; Borai, Anwar; Saleh, Nada A.; Hala, Sharif M.; Saleh, Ayman M.
Abstract: This study was performed to evaluate the protective efficacy of metoclopramide (MCP) against the organophosphates paraoxon (POX)‐ and malathion (MLT)‐induced apoptosis in the murine L929 skin fibroblasts. L929 cells were exposed to either POX (10 nm ) or 1.0 μm MLT in the absence and presence of increased concentrations of MCP. The protective effect of MCP on these organophosphate‐stimulated apoptotic events was evaluated by flow cytometry analysis after staining with annexin‐V/propidium iodide, processing and activation of the executioner caspase‐3, cleavage of the poly‐ADP ribose polymerase, fragmentation of the nucleosomal DNA and disruption of the mitochondrial membrane potential (Δψ). Our results showed that increased doses of MCP alone (≥10 μm ) did not induce apoptosis or activation of caspase‐3. Pretreatment of the cells with MCP attenuated all the apoptotic events triggered by the organophosphate compounds in a dose‐dependent manner reaching 70–80% protection when they were preincubated at 1 and 5 μm of the drug before the addition of POX and MLT, respectively. Interestingly, MCP did not offer a significant protective effect against the cytotoxicity of tumor necrosis factor‐α, cisplatinum, etoposide or paclitaxel, which stimulate apoptosis by various mechanisms, suggesting that the anti‐apoptotic effect of the drug is specific to organophosphates. The strong and specific anti‐apoptotic activity of subclinical doses of MCP against the cytotoxicity of organophosphate compounds suggests its potential clinical application in treating their poisoning. Abstract : We evaluated the protective efficacy of metoclopramide against the organophosphates paraoxon‐ and malathion‐induced apoptosis in L929 skin fibroblasts. Our results showed that metoclopramide was able to attenuate all the apoptotic events triggered by these organophosphates in a dose‐dependent manner, when the cells were preincubated with the drug before the addition of the organophosphate. Metoclopramide did not offer a significant protection against the cytotoxicity of TNF‐α, cisplatinum, etoposide or paclitaxel, suggesting that the anti‐apoptotic effect of the drug is specific to organophosphates.